2020
DOI: 10.1093/nutrit/nuaa101
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional interventions for the management of frailty in older adults: systematic review and meta-analysis of randomized clinical trials

Abstract: Context Although nutrition is considered an important intervention for the management of frailty, the actual effectiveness of interventions addressing nutrition in frail older people remains unclear. Objective The aim for this systematic review was to appraise the evidence regarding the effectiveness of nutritional interventions for the management of frailty in older adults. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 76 publications
0
18
1
Order By: Relevance
“…The significant contribution of nutrition to frailty has also been underlined by some authors [35,37]. However, other researchers have suggested that nutritional interventions delivered alone may not be effective for the management of frailty on older people [49]. As for the psychological domain, previous studies showed that group-based interventions addressing loneliness and social isolation could help to reduce depressive symptoms [41,50].…”
Section: Discussionmentioning
confidence: 95%
“…The significant contribution of nutrition to frailty has also been underlined by some authors [35,37]. However, other researchers have suggested that nutritional interventions delivered alone may not be effective for the management of frailty on older people [49]. As for the psychological domain, previous studies showed that group-based interventions addressing loneliness and social isolation could help to reduce depressive symptoms [41,50].…”
Section: Discussionmentioning
confidence: 95%
“…The significant contribution of nutrition to frailty has also been underlined by some authors [38,40]. However, other researchers have suggested that nutritional interventions delivered alone may not be effective for the management of frailty on older people [66]. As for the psychological domain, previous studies showed that group-based interventions addressing loneliness and social isolation could help to reduce depressive symptoms [45,62].…”
Section: Discussionmentioning
confidence: 95%
“…The significant contribution of nutrition to frailty has also been underlined by some authors [ 38 , 40 ]. However, other researchers have suggested that nutritional interventions delivered alone may not be effective for the management of frailty in older people [ 66 ]. As for the psychological domain, previous studies showed that group-based interventions addressing loneliness and social isolation could help to reduce depressive symptoms [ 45 , 62 ].…”
Section: Discussionmentioning
confidence: 99%